Use of social network sites and compulsive buying behavior: Litterature review using PRISMA (International Journal of Scientific Research and Management (IJSRM), 2025)
Nowadays, it is admitted that buying is not just a simple necessity to fulfill a physical need; it goes beyond that. The buying act also provides satisfaction, pleasure, and instant gratification. In the last decades, purchasing forms have become more differentiated due to the emerging use of the internet and other technological tools. Secondly, with the advent and expansion of social networks, the consumer is facing, during one day, a large flow of information and advertisements that create in him the desire and need to buy, trigger probably the mechanism of self-comparison to others and create confusion about the concept of materialism and identity. These factors mentioned above have been responsible for the purchase decision model (P.Kottler, K.Keller, B.Dubois, D.Manceau, Pearson,2016) and need to be thoroughly followed. This means that these elements can lead to overconsumption and excessive purchases with harmful consequences for some consumers. This paper reviewed compulsive buying and the relationship between social network site use and compulsive purchasing. This review also presented the elements that moderate this relationship. This study aims to shed light on compulsive buying and explore how social network sites can affect consumer behavior and push the individual to make compulsive purchases. The research used a systematic literature review approach based on Scopus, SpringerLink, and JSTOR databases with specific inclusion and exclusion criteria.